CTGF Is Expressed During Cystic Remodeling in the PKD/Mhm (cy/+) Rat Model for Autosomal-Dominant Polycystic Kidney Disease (ADPKD). (December 2017) - Gauer, Stefan; Holzmann, Yvonne; Kränzlin, Bettina; Hoffmann, Sigrid C.; Gretz, Norbert; Hauser, Ingeborg A.; Goppelt-Struebe, Margarete; Geiger, Helmut; Obermüller, Nicholas
Connective tissue growth factor (CTGF, also named CCN2) plays an important role in the development of tubulointerstitial fibrosis, which most critically determines the progression to end-stage renal failure in autosomal-dominant polycystic kidney disease (ADPKD), the most common genetically caused renal disease. We determined CTGF expression in a well-characterized animal model of human ADPKD, the PKD/Mhm (cy/+) rat. Kidneys of 12 weeks old (cy/+) as well as (+/+) non-affected rats were analyzed for CTGF RNA and protein expression by RT-PCR, Northern and Western blot analyses, in situ hybridization, and IHC. Besides the established expression of CTGF in glomerular cells in kidneys of wild-type (+/+) animals, in (cy/+) rats, CTGF mRNA and protein were robustly expressed in interstitial, stellate-shaped cells, located in a scattered pattern underlying the cystic epithelium and in focal areas of advanced tubulointerstitial remodeling. Renal CTGF mRNA and protein expression levels were significantly higher in (cy/+) rats compared with their (+/+) littermates. Detection of CTGF expression in cells adjacent to cystic epithelium and in areas of marked fibrosis suggests a role in the local response to cyst development and indicates that CTGF may be a relevant factor contributing to tubulointerstitial fibrosis in polycystic kidney disease.